High-temperature operation of distributed feedback quantum-cascade lasers at 5.3 µm - Hofstetter, Daniel; Beck, Mattias; Aellen, Thierry; Faist, Jérôme (My University, 2001)
High-temperature operation of a low-threshold 5.3 µm quantum-cascade distributed feedback laser is presented. The emission spectrum was single mode with more than 20 dB side mode suppression ratio for all investigated temperatures and up to thermal rollover. For 1.5% duty cycle and at 0 °C, the laser emitted 1.15 W of single mode peak power; at 120 °C, a value of 92 mW was seen. For a 3 mm long device, we observed a room-temperature threshold current density of 3.6 kA/cm2. This remarkable performance is mainly due to a 4 quantum-well active region using a double phonon resonance for the lower laser level.